Okolice : miesiecznik spoleczno-literacki 10/89. ([Warszawa] : Okolice, 1989)
One issue of a Polish contemporary literary magazine dealing with the latest in Polish literature.
One issue of a monthly magazine, October 1989.
Keywords: Polish literature -- 20th century